Prevention of sudden cardiac death in athletes, sportspersons and marathoners in India - Amit Vora (Indian Heart Journal, 2018)
The annual incidence of sudden cardiac death (SCD) in athletes is significantly lower than the general population. However, when SCD occurs in an athlete during sporting event or training, it sends shockwaves in the society and raises questions about cardiovascular effects of sports and exercise. This document reviews the causes and mechanism of SCD in sports and exercise in young and older athletes. In the Indian context, we suggest a ‘pre-participation screening’ of young and older athletes and consider a ‘supervised, graded exercise regime’ for the uninitiated, older sports participant. Finally, the document proposes medical infrastructure required to successfully revive a victim of sudden cardiac arrest during a sporting event.